PENGARUH KARAKTERISTIK PASIR PANTAI TERHADAP PERSENTASE KEBERHASILAN PENETASAN TELUR PENYU LEKANG (Lepidochelys olivacea) DALAM UPAYA KONSERVASI PENYU DI BALI - Parawangsa, I Nyoman Yoga; Arthana, I Wayan; Ekawaty, Rani (Metamorfosa: Journal of Biological Sciences; Vol 5 No 1 (2018)DO - 10.24843/metamorfosa.2018.v05.i01.p06, 2018)
Six of the seven sea turtle species are found in Indonesia and three of them did their laying eggs process on some of the beaches in Bali, one of which is Olive Ridley sea turtles ( Lepidochelys olivacea ) that goes into the category of endangered by the IUCN. This research aims to study the effect of different characteristics of the sand beach on Olive Ridley sea turtle eggs hatching percentage on the semi natural nest media. Egg hatching success in the samples which were observed through a variable of sand temperature, air temperature, humidity, sand humidity, size of the sand grain and sand colors. The highest percentage of eggs hatching success of the eggs sample was occurred on sand media of Serangan Island Beach by 97% with an incubation period of 49 days and a range of sand temperatures ranged between 27.50 o C until 30.40 o C. While sand media of Saba Beach and Perancak Beach showed percentage of hatching success of 87% and 67% respectively with an incubation period of 46 days. Difference in the incubation period was affected by the variable of sand temperature.  While the difference in hatching percentage success was influenced by a large variable grain of sand in media hatching. By increasing the percentage of high hatching success, it will obtain more live hatchling for the recovery of sea turtle populations in an effort to support turtle conservation activities.